EmploymentWoaftgeerormesaotuicrscetescohfntohloegUiepspfoerTtehme pisque River evaluation of risks ofWfloaotedrshaesdc,oCnosestqauReniccae(oTef ctnhiecal Note) climatic change and the affectations to phytodiversity - Márquez-Gurri, Raimundo (2012)
The global climatic change that takes place in the current times has diverse origins, not causing few polemics and declarations from different areas of knowledge.The floods are part of the consequences of the phenomena that take place when crisis are accentuated and the environment deteriorates. This research presents some experiences in the employment of the geomatics tools for the minimi- zation of risks when there is the possibility of the occurrence of extraordinary events: strong rains in short periods of time and floods, as a consequence of the climatic change, particularizing in the com- munication roads, as antropics elements and the interruption of the natural course of the waters on the topographical relief and the impacts on phito- diversity.